Pendidikan Politik bagi Anak melalui Organisasi Siswa Madrasah Ibtidaiyah - Nur Shofia Hindun; Inayatul Ulya; M Sofyan Alnashr (Dawuh Guru: Jurnal Pendidikan MI/SD, 2021)
Political education for children is a very good provision in shaping the character of children who are responsible. This study aims to describe how the implementation of political education for students at MI Thowalib Pesagen Pati. This research is a qualitative research with a descriptive approach to describe political education for students through the organization of the Madrasah Ibtidaiyah Student Association (ISMI). The results showed that the background for the formation of ISMI was the ideals of the institution to shape the character of students. Political education for students is carried out through various extracurricular activities such as yasinan, tahlilan, compensation, mutual cooperation, commemoration of Islamic holidays, election of the chairman of ISMI, and other social activities. ISMI is able to make its administrators have a character of responsibility, social care, and democratic.